English Medium Instruction (EMI) practice: Higher education internationalization in Indonesia - Simbolon, Nurmala Elmin (Universitas Islam Negeri Banda Aceh, 2021)
Indonesian universities are striving to obtain international recognition in this global competition of higher education. In doing so, many offer English Medium Instruction (EMI) courses. However, there is no documentation of the arrangement of EMI practice in Indonesian universities. This article presents a picture of the current implementation of EMI in some universities as one strategy to obtain international recognition. Survey research is selected to gather some key issues surrounding the implementation of EMI. A questionnaire is administered to 30 universities, and half of them returned the responses. Data analysis uses a descriptive approach. Findings show that the main reason for EMI practice in most Indonesian universities is to address current competition among global universities. Higher education internationalization is indicated in using the English language in two main types of EMI classes: 'Bilingual Class' and 'International Class'. This study also highlights the limited understanding of EMI practice implications in Indonesian universities, especially regarding relevant support given to both EMI students and lecturers. Some key suggestions from the research include incorporating English for Specific Purposes (ESP) in EMI programs and the importance of stimulating collaboration between both content and English lecturers.